Patient characteristics, symptoms, and urodynamic parameters associated with detrusor contraction duration in women - Wang, Connie N.; Ha, Albert; Chung, Doreen E. (Frontiers in Urology, 2023)
Background: There is a lack of understanding of the clinical significance of detrusor contraction duration (DCD) measured on urodynamic studies (UDS). We aimed to identify patient characteristics, presenting symptoms and urodynamic parameters associated with DCD in women. Methods: Using a single-institution database of UDS (2015-2019), 405 female patients with measurable detrusor contractions were identified. Baseline characteristics, presenting symptoms and UDS parameters were analyzed. Bladder outlet obstruction (BOO) was characterized using the Blaivas-Groutz nomogram. Wilcox Rank Sum Tests were used for descriptive statistics, and a univariable generalized linear model conforming to a gamma distribution was used. Results: Median age was 65 years (IQR 52-75), BMI was 27.5 kg/m2 (IQR 23.9-31.1) and DCD was 90 seconds (IQR 57-124). On univariable analysis, degenerative disc disease (β = -17.9, p = 0.02), pelvic radiation (β = -31.91, p = 0.04), and stress incontinence (β = -14.11, p = 0.03) were associated with reduced DCD. Black race was associated with longer DCD (β = 22.92, p = 0.01). Analysis of UDS parameters revealed a significant increase in DCD per unit increase of bladder capacity (β = 0.08, p <0.001), detrusor pressure (Pdet) at maximum flow (Qmax) (β = 0.96, p <0.001), and maximum Pdet (β = 1.2, p <0.001). In contrast, a significant decrease in DCD was noted per unit increase in Qmax (β = -1.43, p <0.001). Finally, mild (β = 34.4, p <0.001), moderate (β = 72.52, p <0.001), and severe (β = 64.6, p <0.001) BOO were all associated with increased DCD. Conclusions: Median DCD in women is 90 seconds. Longer DCD is associated with greater degree of BOO, higher maximum Pdet, Pdet at Qmax, and bladder capacity. Disc disease, irradiation and stress incontinence are associated with reduced DCD. Further studies are needed to evaluate the predictive value of DCD in women.